Conflict Management in Pesantren, Madrasah, and Islamic Colleges in Indonesia: A Literature Review - Lalu Pattimura Farhan; Prosmala Hadisaputra (Jurnal Dialog, 2021)
This is a literature review focusing on the causes and the conflict resolution in pesantren (Islamic boarding schools), madrasas, and Islamic colleges in Indonesia. The study based on 27 documents consisting of 12 documents on conflict management in Islamic boarding schools, 12 documents on conflict management in madrasah and 3 documents on conflict management in Islamic Higher Education. All documents were strictly selected through the following stages: first, keyword mapping; second, searching; third, screening; fourth, checking the sorted data in the Mandeley software; fifth, all existing literatures are imported into the Nvivo software for analysis. The results of the study show that: 1) Among the causes of conflict in the pesantren are mainly family problems within the pesantren, and conflicting views in the management of education; 2) The causes of conflict in madrasah include the discipline of working time, teacher personal styles and personal problems, communication problems, organizational structure, and organizational members, and financial management problems; 3) The causes of conflict in Islamic colleges are disputed opinions and various interests among individuals or groups in the institution. Artikel ini adalah kajian literatur yang fokus mendiskusikan penyebab konflik dan penyelesaiannya dalam manajemen konflik di pesantren, madrasah, dan perguruan tinggi Islam (PTKI) di Indonesia. Jumlah literatur yang direview adalah 27 dokumen; 12 dokumen berbicara mengenai manajemen konflik di pesantren, 12 dokumen tentang manajemen konflik di madrasah, dan 3 dokumen membincangkan manajemen konflik di Perguruan Tinggi Islam. Semua dokumen dikumpulkan secara ketat melalui tahapan-tahapan berikut: pertama, pemetaan kata kunci; kedua, pencarian (searching); ketiga, penyaringan (screening); keempat, memasukkan semua data yang sudah dipilah ke dalam software Mandeley; kelima, semua data/literatur yang ada di Mandeley diimpor ke software Nvivo untuk dianalisis. Hasil kajian menunjukkan bahwa: 1) Di antara penyebab konflik di pesantren adalah masalah keluarga di internal pesantren, perbedaan pendidikan dan pandangan manajemen; 2) Penyebab konflik di madrasah antara lain kedisiplinan kehadiran dan waktu kepulangan, gaya pribadi guru, dan masalah pribadi, masalah komunikasi, struktur organisasi, dan anggota organisasi, dan masalah manajemen keuangan; 3) Di antara penyebab konflik di perguruan tinggi Islam adalah perbedaan pendapat dan kepentingan antara individu atau kelompok.